2014
DOI: 10.1167/iovs.13-13236
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values for Corneal Densitometry Analysis by Scheimpflug Optical Assessment

Abstract: This add-on to the standard imaging software allows rapid and objective assessment of the corneal densitometry. We provide normative data that may be used as a reference facilitating research and complementing clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
193
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(236 citation statements)
references
References 27 publications
36
193
6
1
Order By: Relevance
“…This zone is the area with the poorest repeatability and reproducibility of the measurements. 14 Previous studies reported corneal densitometry values of 16.76 ± 1.87 GSU, which is similar to our preoperative values: 16.62 ± 1.97 for LASIK, 16.38 ± 1.67 for PRK, and 16.26 ± 1.50 for ReLEx SMILE. 15,16,30 Previous studies have also evaluated corneal densitometry in PRK and LASIK patients both before and after surgery.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This zone is the area with the poorest repeatability and reproducibility of the measurements. 14 Previous studies reported corneal densitometry values of 16.76 ± 1.87 GSU, which is similar to our preoperative values: 16.62 ± 1.97 for LASIK, 16.38 ± 1.67 for PRK, and 16.26 ± 1.50 for ReLEx SMILE. 15,16,30 Previous studies have also evaluated corneal densitometry in PRK and LASIK patients both before and after surgery.…”
Section: Discussionsupporting
confidence: 90%
“…15,16,30 Previous studies have also evaluated corneal densitometry in PRK and LASIK patients both before and after surgery. [14][15][16] As for post-PRK patients, the 3-month postoperative value was 37.81 GSU, and the 12 month one was 26.92 GSU, 15 which is twice the value found in our study. Fares et al 16 found no significant differences between pre-and postoperative values for overall corneal densitometry following LASIK, and reported corneal densitometry values 12 months after surgery that were slightly lower than our results.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Mean corneal densitometry in healthy adults has been recently reported as 12.3±2.4 and 19.7±3.9 GSU in two different studies. 6,7 The right and left corneal densitometry values were also found to be highly correlated in a previous study. 7 However, the corneal densitometry of our patient was 18.6 GSU in the affected eye and 15.7 GSU in the fellow eye.…”
Section: Discussionsupporting
confidence: 55%
“…The study added a large group of Asians, to the best of our knowledge this is the first study to report normal values of corneal densitometry on Asian cornea. Previous studies were done with Caucasians [20] and Chinese Participants [21]. Limitation of this study was small number of participants in groups' age above 60.…”
Section: Discussionmentioning
confidence: 98%